Elevated levels of autophagy-related marker ULK1 and mitochondrion-associated autophagy inhibitor LRPPRC are associated with biochemical progression and overall survival after androgen deprivation therapy in patients with metastatic prostate cancer. Issue 5 (27th September 2016) - Zhang, Hong-Yi; Ma, Ya-Dong; Zhang, Ye; Cui, Jie; Wang, Zi-Ming
Abstract : Aim: To evaluate the expression levels and prognostic significance of autophagy-related markers, UNC-51-like kinase1 (ULK1), Beclin1, microtubule-associated protein light chain 3 (LC3), autophagy-related gene 5 (ATG5) and mitochondrion-associated autophagy inhibitor, LRPPRC, in patients with metastatic prostate cancer (PCa) after androgen deprivation therapy (ADT). Methods: Expressions of ULK1, Beclin1, LC3, ATG5 and LRPPRC were assessed by immunohistochemical examination in 198 patients with metastatic PCa who were receiving ADT (goserelin and bicalutamide). Results: High expression levels of LRPPRC and ULK1were significantly associated with Gleason score, serum prostate-specific antigen (PSA) levels, PSA levels after ADT and number of metastatic sites. High expression of ULK1 in patients with concomitant high expression of LRPPRC was significantly associated with multiple metastases, shorter biochemical progression (BCP)-free survival and shorter overall survival (OS). ULK1 expression, LRPPRC expression, Gleason score, PSA levels after ADT and number of metastatic sites were independently associated with shorter BCP-free survival and OS on multivariate analysis. Furthermore, two-year BCP rate of patients with ≥3 risk factors was found to be significantly higher as compared with that of patients with ≤1 and 2 risk factors. Three-year OS rate in patients with ≥3 risk factors was significantly lower than that of those with ≤1 and 2 risk factors. Conclusions: High expression of ULK1 concomitant with high expression of LRPPRC may serve as useful markers for shorter BCP-free survival and OS in patients with metastatic PCa after ADT.